Bainaimiao Arc as an Exotic Terrane Along the Northern Margin of the North China Craton: Evidences From Petrography, Zircon U‐Pb Dating, and Geochemistry of the Early Devonian Deposits. Issue 8 (1st August 2019) - Ma, Shouxian; Wang, Zongqi; Zhang, Yingli; Sun, Jianxun
Abstract: As one of the most important Early Paleozoic arc systems in the Central Asian Orogenic Belt, the tectonic affinity of the Bainaimiao arc belt is highly controversial. This study performed paleocurrent, petrography, trace elements of the whole rocks and U‐Pb geochronology of tuff and detrital zircons of the Early Devonian deposits, to constrain the tectonic affinity of the Bainaimiao arc belt. New zircon U‐Pb age constrains the Xibiehe Formation to the Early Devonian. Both the Xibiehe and Qiankuntougou formations show similar framework mineral and trace element components, suggesting a dissected ensialic island arc source. However, the U‐Pb age spectra of detrital zircons for the two formations are totally different. The Xibiehe Formation reflects continuous ages ranging 1977–597 Ma, indicating the Bainaimiao arc origin. The Qiankuntougou Formation has a mixed source displaying the North China Craton‐derived ages (~1.85 and ~2.52 Ga) and Bainaimiao arc ages (~1.4, ~1.2, ~0.97, 0.55, and 0.5–0.43 Ga). The comparable age components indicate that the Bainaimiao arc is an exotic terrane accreted to the North China Craton in an arc‐continent collision way at ca. 430–410 Ma. The arc‐continent collision and the following postorogenic magmatism (410–360 Ma), sedimentation during extensional collapse and south dipping subduction complex evolution imply a subduction polarity flip from the northward subduction to the southward subduction. Key Points: The Xibiehe Formation was formed at 405 ± 2 Ma, coeval with the Qiankuntougou Formation in the Early Devonian The Xibiehe Formation sourced from the Bainaimiao arc, while the Qiankuntougou Formation sourced from both the Bainaimiao arc and North China Craton The Bainaimiao arc is an exotic terrane accreted to the northern margin of the North China Craton at ca. 430–410 Ma